Service architecture for multi-environment mobile cloud services. (2016) - Houacine, Fatiha; Bouzefrane, Samia; Adjaz, Aghiles
The growth of connected devices, mostly due to the large number of internet of things (IoT) deployments and the emergence of mobile cloud services, introduces new challenges for the design of service architectures in mobile cloud computing (MCC). An MCC framework should provide elasticity and scalability in a distributed and dynamic way while dealing with limited environment resources and variable mobile contexts (web applications, real-time, enterprise services, mobile to mobile, hostile environment, etc.) that may include additional constraints impacting the design foundation of cloud services. We show in this work how service-oriented architecture (SOA) can be a key solution to provide distributed mobile cloud services and how OSGi platform can be an adaptive and efficient framework to provide such implementation. We adapt the proposed MCC framework to different architecture contexts. The first one is a traditional centric model, where mobile devices are reduced to consuming services. The second one is a distributed model where the power of mobile-to-mobile interaction offers unlimited value-services opportunities, and finally, three-tier architecture is considered with the introduction of the cloudlet notion. For each context, we explore the performance of our service-oriented framework, and contrast it with alternative existing solutions.